PROBABILISTIC-TEMPORAL CHARACTERISTICS AND PERFORMANCE LIMITATIONS OF SOFTWARE-DEFINED NETWORK CONTROLLERS - Nabiyeva Аsmar (Collection of scientific papers «ΛΌГOΣ», 2025)
The paradigm of Software-Defined Networks (SDN) represents a significant shift in network management and operation, offering programmability and flexibility by separating the control plane from the data plane. Despite its wide adoption, SDN faces inherent challenges related to probabilistic and temporal performance characteristics, particularly regarding the scalability of controllers and their ability to manage network nodes.